Mengurai Eksistensi Lingkungan Pendidikan Islam Perspektif Sosiologis - Murdianto, Murdianto (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2018)
The environment of religious education is a means that can provide motivation, educational facilities, the vehicle of self potential learners development effective-efficient value by development, needs, as well as provide guidance and serious attention to the moral spiritual needs. The article entitled unravel the existence of Sociological perspective of Islamic Educational Environments there are three elements, families, schools, andcommunities. The third element of the responsibility for progress or setbacks of Islamic education. As well as being a unified whole and complementary and should be able to carry out its function as a means of motivating, educational facilities, the vehicle of potential development.